On the cure kinetics modeling of epoxy-anhydride systems used in glass reinforced pipe production - Flores, Hugo Alejandro (2013)
Aiming to determine a suitable model to describe the curing kinetics of a commercial epoxy/anhydride initiated by a quaternary amine system used for the production of glass reinforced pipes, calorimetric and infrared spectroscopic kinetics data were collected. Several phenomenological, isoconversional and mechanistics kinetics models were revisited and tried. In addition, the time-temperature-transformation diagram, which is fundamental for the design of curing cycles, was assessed from calorimetric and gel time experiments. It was found that the Kamal´s model and a mechanistic model comprising an activation reversible step followed by a propagation step (Mauri et al., 1997) were capable to well describe all the experimental data. The kinetics mechanism appeared to be independent of the initiator concentration as suggested by the constancy of the apparent activation energy obtained by the Kissinger´s method. According to the mechanistic model, the activation step resulted independent on initiator concentration while propagation rate accelerated with increasing it. The presence of glass fiber reinforcement did no affect the curing kinetics of the studied reactive system.